The Exogenous Effect of Geography on Economic Development: The Case of Sub-Saharan Africa. - Tang, Min; Woods, Dwayne (African & Asian Studies, 2008)
This article examines the relevance of geography and climate in the economic development and underdevelopment of Sub-Saharan African countries. We conceptualize geography and climate as exogenous factors determining a country's overall economic welfare. By employing the newly compiled G-econ dataset with a better measurement of geography, we found that, even controlling for institutional and social factors, geography plays a substantial role in explaining some aspects of Africa's poverty. This finding indicates that we need to partly reformulate the policy prescriptions for African economic development that are based heavily on institutionalist explanations of bad governance and corruption.